A human milk oligosaccharide, 2′-fucosyllactose, enhances the immunity in mice fed an infant formula milk diet. (November 2019) - Mao, Xiao; Wang, Jianwu; Hang, Yuanxin; Zhang, Yanchun; Yu, Huanhuan; Li, Ze; Pan, Lina; Zhiyong Dai,
Abstract: The immune effect of 2′-fucosyllactose (2′FL) in mice fed an infant formula (IF) milk diet was studied. Forty-five BALB/C mice were randomly divided into 3 groups: control, and low and high dose of 2′FL. 2′FL was administered once daily for 30 days and all the mice were fed IF milk diet. On day 30, the spleen and thymus were isolated and weighed for immune organ index calculation. Natural killer (NK) cell activity, T-lymphocyte proliferation capacity and delayed-type hypersensitivity reactivity (DTH) were measured. There was a significant increase in thymus index in high dose 2′FL group ( p  < 0.05). T-lymphocytes in high dose 2′FL group also tended to proliferate more compared with the control group ( p  < 0.05). NK cell activity and the degree of DTH were improved in both 2′FL groups ( p  < 0.05). These data demonstrated that 2′FL can improve immunity in mice fed an IF milk diet.